2012
DOI: 10.1002/hbm.21499
|View full text |Cite
|
Sign up to set email alerts
|

Corpus callosum damage predicts disability progression and cognitive dysfunction in primary‐progressive MS after five years

Abstract: We aim to identify specific areas of white matter (WM) and grey matter (GM), which predict disability progression and cognitive dysfunction after five years in patients with primary-progressive multiple sclerosis (PPMS). Thirty-two patients with early PPMS were assessed at baseline and after five years on the Expanded Disability Status Scale (EDSS), and EDSS step-changes were calculated. At year five, a subgroup of 25 patients and 31 healthy controls underwent a neuropsychological assessment. Baseline imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 52 publications
(66 reference statements)
7
31
0
Order By: Relevance
“…In addition, a recent study in RRMS patients, reported that, compared to healthy controls, there was a reduction in the connectivity of various regions in MS patients, particularly in the frontal and hippocampal regions, the motor strip, and occipital lobes (Li et al, 2013). Similarly, another recent study in PPMS patients found that a lower fractional anisotropy (FA) in the splenium of the corpus callosum predicted a greater progression of disability after 5 years (Bodini et al, 2013). Also, in this study a lower FA along the entire corpus callosum predicted worse verbal memory, attention, and information processing speed.…”
Section: Diffusion Mrimentioning
confidence: 99%
“…In addition, a recent study in RRMS patients, reported that, compared to healthy controls, there was a reduction in the connectivity of various regions in MS patients, particularly in the frontal and hippocampal regions, the motor strip, and occipital lobes (Li et al, 2013). Similarly, another recent study in PPMS patients found that a lower fractional anisotropy (FA) in the splenium of the corpus callosum predicted a greater progression of disability after 5 years (Bodini et al, 2013). Also, in this study a lower FA along the entire corpus callosum predicted worse verbal memory, attention, and information processing speed.…”
Section: Diffusion Mrimentioning
confidence: 99%
“…5 Recently, DTI studies in adult patients with MS demonstrated axonal and myelin injury occurring much earlier in the course of the disease than previously assumed. 6,7 Physiologic myelination is known to expand well into early adulthood in conjunction with cognitive, behavioral, emotional, and motor development. [8][9][10] Any pathology interfering with this process of myelination is likely to affect white matter integrity as has been shown in hypoxic-ischemic encephalopathy, former premature in-fants, and normal-pressure hydrocephalus.…”
mentioning
confidence: 99%
“…Infarction of the SPCC and retrosplenial region can lead to verbal memory problems 52, 53, 54. In patients with multiple sclerosis, verbal learning performance was inversely associated with lesions in the SPCC, lower FA in SPCC predicted a greater progression of disability, and lower FA in the corpus callosum predicted worse verbal memory, longitudinally over 5 years 55, 56…”
Section: Discussionmentioning
confidence: 99%